The mechanism of nucleosome traversal by RNA polymerase II: Roles for template uncoiling and transcript elongation factors - Luse, Donal S (Landes Bioscience, 2011)
RNA polymerase II traverses nucleosomes rapidly and efficiently in the cell but it has not been possible to duplicate this process in the test tube. A single nucleosome has generally been found to provide a strong barrier to transcript elongation in vitro. Recent studies have shown that effective transcript elongation can occur on nucleosomal templates in vitro, but this depends on both facilitated uncoiling of DNA from the octamer surface and the presence of transcription factors that maintain polymerase in the transcriptionally competent state. These findings indicate that the efficiency and rate of transcription through chromatin could be regulated through controlled DNA uncoiling. These studies also demonstrate that nucleosome traversal need not result in nucleosome displacement.